Less is more: Optimised fire performance in glass fibre-reinforced polybutylene terephthalate laminates with concentrated flame retardant top layer - Weronika Tabaka; Bernhard Schartel (Composites Part C: Open Access)
To achieve optimum fire performance while maintaining mechanical integrity, flame retardants (FR) were strategically concentrated in the surface layer of a two-layer glass fibre-reinforced polybutylene terephthalate (PBT) laminate structure. Three potentially synergistic FR systems were selected to improve the fire performance of glass fibre-reinforced PBT: boehmite (AlOOH) with melamine polyzinc phosphate (MPZnP), aluminium diethyl phosphinates (AlPi) with melamine cyanurate (MC), and expandable graphite (EG) with melamine polyphosphate (MPP). Limited Oxygen Index (LOI) and UL-94 testing highlighted the influence of laminate architecture on flammability. The cone calorimeter results showed that increasing the FR concentration in the top layer significantly reduced both the peak heat release rate (PHRR) and the maximum average rate of heat emission (MARHE), with improvements depending on the specific FR system used. The laminate L-PBT/GF/AlOOH/MPZnP with a 2:2 thickness ratio showed outstanding performance, achieving a 45 % reduction in MARHE compared to composites with uniform FR distribution. This result showcases the superior thermal barrier properties and synergistic behaviour of AlOOH and MPZnP. The fire performance of laminates containing AlPi and MC was strongly influenced by the distribution and concentration of AlPi/MC. The EG/MPP system was found to be highly effective, forming a protective intumescent layer that significantly reduced both HRR and MARHE, demonstrating the effectiveness of strategically concentrating FR in the top layer.